Translation Issues of Linguocultural Aspects of Gender Lexis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the author discusses the linguocultural features activated through gender-related lexical units in English and Uzbek literature, including the use of phraseological expressions in the language of literary works, the representation of religious concepts closely connected with people’s daily lives in creating artistic imagery, and the issues of recreating these elements in translation. As the main sources of analysis, the author refers to Margaret Mitchell’s “Gone with the Wind”, Charlotte Brontë’s “Jane Eyre”, and Theodore Dreiser’s “Sister Carrie”.